Manajemen Peningkatan Mutu Lembaga Pendidikan Perguruan Diniyyah Puteri Padang Panjang - Atika, Atika; Febriyani, Irma; Wahyuni, Sri Intan; Arifin, Zainal (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2023)
Diniyyah Puteri College as one of the oldest Islamic boarding schools for women, which was established in 1923, has been able to maintain its existence in the midst of the existence of new pesantren with their respective characteristics. This study examines improving the quality of female diniyyah education from early childhood to higher education. Research data obtained through in-depth interviews, active participation, and documentation. This study found that the Diniyyah Puteri College applied the concept of TQM (Plan, Do, Study, Act) in improving the quality of education. The main goal of all levels of education at the Diniyyah Puteri College is the achievement of the vision of the Diniyyah Puteri College, which is to become a center for modern Islamic education based on the Qur'an and Sunnah that produces works on the world stage.